Curcumin modified silver nanoparticles for highly efficient inhibition of respiratory syncytial virus infection. Issue 5 (19th January 2016) - Yang, Xiao Xi; Li, Chun Mei; Huang, Cheng Zhi
Abstract : Uniform and stable curcumin-AgNPs, which are synthesized with a simple method, show excellent antiviral properties against respiratory syncytial virus. Abstract : Interactions between nanoparticles and viruses have attracted increasing attention due to the antiviral activity of nanoparticles and the resulting possibility to be employed as biomedical interventions. In this contribution, we developed a very simple route to prepare uniform and stable silver nanoparticles (AgNPs) with antiviral properties by using curcumin, which is a member of the ginger family isolated from rhizomes of the perennial herb Curcuma longa and has a wide range of biological activities like antioxidant, antifungal, antibacterial and anti-inflammatory effects, and acts as reducing and capping agents in this synthetic route. The tissue culture infectious dose (TCID50 ) assay showed that the curcumin modified silver nanoparticles (cAgNPs) have a highly efficient inhibition effect against respiratory syncytial virus (RSV) infection, giving a decrease of viral titers about two orders of magnitude at the concentration of cAgNPs under which no toxicity was found to the host cells. Mechanism investigations showed that cAgNPs could prevent RSV from infecting the host cells by inactivating the virus directly, indicating that cAgNPs are a novel promising efficient virucide for RSV.